FACTORS AFFECTING IN VITRO SHOOT AND MICRORHIZOME INDUCTION OF CURCUMA LATIFOLIA ROSC. AND CURCUMA COMOSA ROXB., THAI MEDICINAL PLANTS FOR WOMEN’S HEALTH - Prathanturarug, S.; Lo-apirukkul, S.; Saralamp, P.; Jenjittikul, T. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
In vitro propagation methods have for the first time been developed for wan chak motluk (Curcuma comosa Roxb. and Curcuma latifolia Rosc.), which is widely used for women’s health in Thai traditional medicine. The effects of plant growth regulators (TDZ, BA, and NAA) have been investigated for multiple shoot induction using undivided and divided terminal bud explants. High frequency shoot multiplications were obtained when the undivided explants of C. latifolia Rosc. and C. comosa Roxb were cultured on semi-solid Murashige and Skoog (MS) medium supplemented with 36.32 and 18.16 ?M TDZ, respectively, for 8 weeks prior to transfer to MS medium without PGR for 4 weeks. Shoot regeneration rates were 18.38±2.28 and 11.82±1.03 shoots/response explant, respectively. Rooting was spontaneous achieved. Rooted plantlets were successfully transferred to soil. Microrhizome induction was influenced by plant species, carbohydrate source, and plant growth regulators. Liquid MS medium with 8.87M BA and 70 g/l sucrose or 17.76M BA and 50 g/l sucrose were optimal for the microrhizome induction of C. latifolia Rosc and C. comosa Roxb respectively. After 12 weeks of culture, Microrhizome induction rates were 4.92±0.28 and 3.36±0.44 microrhizomes/response explant, respectively. An anatomical study demonstrated that starch accumulation in microrhizomes increased when the concentration of sugar was elevated and duration of culture extended. The microrhizomes were germinable under greenhouse conditions and further developed into normal plants. The established protocols will be used for the production of uniform plantlets suitable for field plantation for the herbal industry.